Cardiorespiratory and perceptual responses of two interval training and a continuous training protocol in healthy young men (2019)
High Intensity Interval Training (HIIT) can be performed with different effort to rest time-configurations, and this can largely influence training responses. The purpose of the study was to compare the acute physiological responses of two HIIT and one moderate intensity continuous training (MICT) protocol in young men. A randomised cross-over study with 10 men [age, 28.3 ± 5.5years; weight, 77.3 ± 9.3 kg; height, 1.8 ± 0.1 m; peak oxygen consumption (VO 2 peak), 44 ± 11 mL.kg ?1 .min ?1 ]. Participants performed a cardiorespiratory test on a treadmill to assess VO 2 peak, velocity associated with VO 2 peak (vVO 2 peak), peak heart rate (HRpeak) and perceived exertion (RPE). Then participants performed three protocols equated by distance: Short HIIT (29 bouts of 30s at vVO 2 peak, interspersed by 30s of passive recovery, 29 min in total), Long HIIT (3 bouts of 4 min at 90% of vVO 2 peak, interspersed by 3 min of recovery at 60% of vVO 2 peak, 21 min in total) and MICT (21 min at 70% of vVO 2 peak). The protocols were performed in a randomised order with ?48 h between them. VO 2 , HRpeak and RPE were compared. VO 2 peak in Long HIIT was significantly higher than Short HIIT and MICT (43 ± 11 vs 32 ± 8 and 37 ± 8 mL.kg ?1 .min ?1 , respectively, P and lt; 0.05), as well as peak HR (181 ± 10 vs 168 ± 8 and 167 ± 11, respectively, P and lt; 0.05), and RPE (17 ± 4 vs 14 ± 4 and 15 ± 4, respectively, P and lt; 0.05), with no difference between Short HIIT and MICT. In conclusion, Long HIIT promoted higher acute increases in VO 2 , HR and RPE than Short HIIT and MICT, suggesting a higher demand on the cardiorespiratory system. Short HIIT and MICT presented similar physiologic and perceptual responses, despite Short HIIT being performed at higher velocities. © 2018, © 2018 European College of Sport Science.